VD_FINDINFO HC / 2010 / 445 vom 20. April 2010 - VD Tribunal cantonal (2010)
PEINE PÉCUNIAIRE, RÉVOCATION DU SURSIS, SURSIS À L'EXÉCUTION DE LA PEINE, FIXATION DE LA PEINE | 34 al. 2 CP, 42 al. 1 CP, 46 al. 1 CP, 47 CP